Mitophagy in cardiovascular homeostasis. (June 2020) - Zhang, Ruohan; Krigman, Judith; Luo, Hongke; Ozgen, Serra; Yang, Mingchong; Sun, Nuo
Highlights: Mitophagy is a specialized autophagic pathway that mediates the lysosomal clearance of damaged mitochondria. Mitophagy plays a critical role in cardiovascular health. Multiple distinct mechanisms regulate mitophagy. Pharmacological approaches targeting mitophagy may have significant therapeutic benefits for cardiovascular disease. Abstract: Mitochondria are essential organelles that generate energy to fuel myocardial contraction. Accumulating evidence also suggests that, in the heart, mitochondria may contribute to specific aspects of disease progression through the regulations of specific metabolic intermediates, as well as the transcriptional and epigenetic states of cells. If damaged, the mitochondria and their related pathways are hindered, which may result in or contribute to the development of a wide range of cardiovascular diseases. Therefore, the maintenance of cardiac mitochondrial function and integrity through specific mitochondrial quality control mechanisms is critical for cardiovascular health. Mitophagy is part of the overall mitochondrial quality control process, and acts as a specialized autophagic pathway that mediates the lysosomal clearance of damaged mitochondria. In response to cardiac stress and injury, the pathways associated with mitophagy are triggered resulting in the removal of damaged mitochondrial, thereby maintaining cardiac homeostasis. In addition, recent studies have demonstrated an essential role for mitophagy in both developmental and disease-related metabolic transitioning of cardiac mitochondria. Here, we discuss the physiological and the pathological roles of mitophagy in the heart, the underlying molecular mechanisms, as well as potential therapeutic strategies based on mitophagic modulation.